Practical lighting design with LEDs - Lenk, Ron, ....-; Lenk, Carol, ....- (Hoboken (N.J.) : Wiley, 2017)
The essential how-to guide to designing and building LED systems, revised and updated The second edition of Practical Lighting Design with LEDs has been revised and updated to provide the most current information for developing light-emitting diodes products. The authors, noted authorities in the field, offer a review of the most relevant topics including optical performance, materials, thermal design and modeling and measurement. Comprehensive in scope, the text covers all the information needed to design LEDs into end products. The user-friendly text also contains numerous drawings and schematics that show how things such as measurements are actually made, and show how circuits actually work. Designed to be practical, the text includes myriad notes and illustrative examples that give pointers and how-to guides on many of the book's topics. In addition, the book s equations are used only for practical calculations, and are kept at the level of high-school algebra. This thoroughly expanded second edition offers: New chapters on the design of an LED flashlight, USB light, automotive taillight, and LED light bulbsA practical and user-friendly guide with dozens of new illustrationsThe nitty-gritty, day-to-day engineering and systems used to design and build complete LED systemsAn essential resource on the cutting-edge technology of Light-Emitting Diodes Practical Lighting Design with LEDs helps engineers and managers meet the demand for the surge in usage for products using light-emitting diodes with a practical guide that takes them through the relevant fields of light, electronic and thermal design.
Keywords: Electric lighting -- Design; Light emitting diodes